2001
DOI: 10.1002/ana.10052
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylaspartate is an axon‐specific marker of mature white matter in vivo: A biochemical and immunohistochemical study on the rat optic nerve

Abstract: Axonal pathology is a major cause of neurological disability in multiple sclerosis. Axonal transection begins at disease onset but remains clinically silent because of compensatory brain mechanisms. Noninvasive surrogate markers for axonal injury are therefore essential to monitor cumulative disease burden in vivo. The neuronal compound N-acetylaspartate, as measured by magnetic resonance spectroscopy, is currently the best and most specific noninvasive marker of axonal pathology in multiple sclerosis. The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 42 publications
2
81
0
1
Order By: Relevance
“…They found the highest levels of NAA in mature oligodendrocytes differentiated with ciliary neurotrophic factor and in oligodendrocyte-type 2 astrocyte progenitor cells. Optic nerve transection studies in rats have shown that NAA levels in the nerves are completely eliminated 24 days post-transection (Bjartmar et al, 2002). In the same study, retinal ablation on postnatal day 4 suggested that approximately 20% of the NAA in the optic nerve at day 14, and 5% of the NAA at day 20 was derived from proliferating oligodendrocyte progenitor cells.…”
Section: Naa Synthesismentioning
confidence: 90%
See 1 more Smart Citation
“…They found the highest levels of NAA in mature oligodendrocytes differentiated with ciliary neurotrophic factor and in oligodendrocyte-type 2 astrocyte progenitor cells. Optic nerve transection studies in rats have shown that NAA levels in the nerves are completely eliminated 24 days post-transection (Bjartmar et al, 2002). In the same study, retinal ablation on postnatal day 4 suggested that approximately 20% of the NAA in the optic nerve at day 14, and 5% of the NAA at day 20 was derived from proliferating oligodendrocyte progenitor cells.…”
Section: Naa Synthesismentioning
confidence: 90%
“…Axons in many fiber tracts were moderately stained for NAA, including the corpus callosum, corticospinal tracts, optic nerves and tracts, lateral olfactory tracts and stria terminalis (Moffett and Namboodiri, 1995). HPLC studies have confirmed the presence of NAA in optic nerves (Bjartmar et al, 2002). High levels of NAA have also been observed in cerebellar cortex, including the Purkinje cell layer, the granule cell layer and the molecular layer (Simmons et al, 1991).…”
Section: Naa Synthesismentioning
confidence: 91%
“…This indicates that the tNA-Aq concentration in these VOIs actually increased as R1 and R2 decreased. Since tNA is considered a marker of neuronal density (138,(172)(173)(174) this result suggests that there was a process of demyelination, indicated by decreased R1 and R2, without neuronal loss in these patients. The neuronal density of the tissue (per volume) may in fact increase as myelin diminishes, caused by a net shrinkage of the tissue, leading to more axons inside the VOI.…”
Section: Normal Appearing White Mattermentioning
confidence: 98%
“…After the initial oedema resolves, lesions which remain elevated in T1 have shown lower levels of N-acetyl-aspartate (NAA), which is considered a marker of neuronal integrity, and increased concentration of cholin, which is considered a marker of cell membrane turnover (138,(171)(172)(173)(174)(175). These correlations suggest that a persisting elevation of T1 may be related to axonal damage in the lesion (138).…”
Section: Qmri In Msmentioning
confidence: 99%
“…Reduced NAA correlates with the extent of histopathologic axonal loss. 99,109 Anatomically, myelin begins to envelop axons close to the neuronal cell body where it is a potential target of the disease process in MS. Purely intracortical and subpial plaques are well documented pathologically 23,110 and are rarely found by conventional MRI. 110,111 Their detection is improved by FLAIR MRI.…”
Section: Mr Spectroscopymentioning
confidence: 99%